A Chronic Hemophilia Patient With Manifestations of Spontaneous Penile Bleeding and Multiarthropathy - Eka Dharma Putra, I Putu (International Journal of Psychology and Health Science, 2025)
Hemophilia A is a hereditary bleeding disorder characterized by Factor VIII deficiency, with varying severity levels. This report presents a 27-year-old male patient with moderate Hemophilia A who experienced spontaneous penile bleeding and a history of multiarthropathy. The patient reported recurrent bleeding episodes since childhood and received Factor VIII therapy, resulting in significant symptom relief. This case highlights the importance of individualized management in chronic hemophilia, focusing on preventive measures to mitigate future bleeding episodes and comorbidities, thereby improving quality of life and life expectancy. Case report : A 27-year-old male patient presented with spontaneous penile bleeding triggered by minor trauma and associated with moderate Factor VIII deficiency (1%). Past medical history included recurrent joint and gastrointestinal bleeding episodes. The patient responded positively to Factor VIII therapy and packed red cell transfusions, with symptom resolution after 10 days of hospitalization. Family pedigree analysis and coagulation studies confirmed the diagnosis of moderate Hemophilia A. Discussion : Hemophilia A patients face lifelong bleeding risks, with multiarthropathy as a common complication. Factor VIII levels closely correlate with disease severity and bleeding manifestations. Preventive therapy, including Factor VIII administration, is crucial for minimizing complications. Additionally, managing viral infection risks is essential due to associated sexual behavior in certain demographics. Regular screening and patient education play pivotal roles in comprehensive care. Conclusion : This case underscores the significance of proactive management in moderate Hemophilia A, emphasizing tailored therapy and preventive strategies. Ensuring adequate access to clotting factor concentrates and addressing comorbidities can significantly enhance the quality of life and prognosis for chronic hemophilia patients.